Fabrication of durable, fluorine-free superhydrophobic cotton fabric for efficient self-cleaning and heavy/light oil-water separation - Pal, Sukanta; Mondal, Sourav; Pal, Prasanta; Das, Ajit; Pramanik, Subhamay; Maity, Jayanta (Colloid and interface science communications, 2021)
Straightforward and adaptable, superhydrophobic texture with predominant mechanical and chemical robustness has been prepared by a simple and fluorine-free dip-coating method using TiO2 and 3-(trimethoxysilyl) propyl methacrylate. The as-prepared cotton fabric displays strong resistance against different physical, chemical durability and, acid-base corrosions without losing its hydrophobic properties. Self-cleaning conduct of cotton fabric covered with TIO2NPs/silane has additionally appeared. Therefore, the super-hydrophobic/superoleophilic texture is used for deep effective and ultra-fast and micro-to-macro level light oil and heavy oil containing two-phase oil/water separation. In addition, regardless of the concentration, viscosity, and surface tension of the oil-water phase, the treated fabric can separate the oil with high separation efficiency from the three phases of the oil/water mixture. More importantly, even after many separation cycles, the modified fabric still has good reusability and recyclability. Hence, this modified fabric has the advantages of a simple and facile low-cost fabrication procedure, good separation performance, and excellent reusability. [Display omitted] •We fabricated TiO2/Silane based superhydrophobic fabric by a simple and facile fluorine-free dip-coating method.•Mirror-like both-faced superhydrophobic fabric showed good chemical, mechanical, and washing durability.•Functional textile fabric showed remarkable self-cleaning and oil-water separation performance.•The fabricated superhydrophobic fabric was reusable and biodegradable.